WOS (2013-2023) knowledge graphs analysis of literature on intangible cultural heritage / Liu Qi, Zulkifli Abd Latiff, and Wardatul Hayat Adnan - Qi, Liu; Abd Latiff, Zulkifli; Adnan, Wardatul Hayat (Faculty of Information Management, 2023)
The in-depth research on intangible cultural heritage, a large amount of research literature has emerged. In order to better reveal its research trends, this research paper maps and analyses the number of publications, authors, institutions, keyword clustering, and timeline of intangible cultural heritage literature in the Web of Science core collection from 2013 to 2023 by using Citespace, a software for knowledge graphs. The map visualises the frontiers of intangible cultural heritage research, major research fields, important literature, important scholars, and research hotspots. This study found that although there is cooperation between institutions and scholars, cooperation still needs to be strengthened. The scope of research is gradually becoming increasingly extensive and combined with emerging scientific and technological developments, which will be an important direction for future research. Under the expansion of technology, intangible cultural heritage will be affected by many factors, including impact, transformation, and how to apply it. This requires scholars to carefully explore. The exchange and collision between cultures, the re understanding of national consciousness and cultural identity by different countries, ethnic groups, and groups, as well as the integration, development, and utilisation of cultural industries with other industries, and the continuous emergence of new problems are still ongoing and may never end. Scholars need to go a long way. This study analyses many notable achievements and hot areas, which are useful for future researchers to better grasp the trends in the field of intangible cultural heritage.